All-manganese-based Li-ion batteries with high rate capability and ultralong cycle life. (April 2016) - Wang, Jian-Gan; Jin, Dandan; Liu, Huanyan; Zhang, Cunbao; Zhou, Rui; Shen, Chao; Xie, Keyu; Wei, Bingqing
Abstract: High-rate and long-cycle life Li-ion batteries constructed with all-manganese-based electrode materials have been successfully realized. The key to the success is the facile green synthesis of the anode: MnO@C core–shell nanowires with internal void spaces and a uniform carbon coating shell. The unique one-dimensional nano-configuration provides reduced solid-state distance for Li-ion/electron transport, enhanced electrical conductivity for charge transfer, and effectively volumetric accommodation for Li-ion insertion/extraction, thus enabling the MnO@C nanostructures to exhibit high-rate Li-ion storage capacity and long cycling stability. When coupled with a nanostructured LiMn2 O4 cathode, the all-manganese-based MnO@C∥LiMn2 O4 full cell characterizes a high energy density of 397 Wh kg −1, high rate capability (215 Wh kg −1 at a power density of 6.2 kW kg −1 ), and an extremely low decay rate of 0.087% per cycle over 1000 cycles. Combining with additional merits of low cost, eco-friendliness, and safe operation, our design will shed light on fabricating high-performance Li-ion batteries from all manganese-based electrode materials. Graphical abstract: An all-manganese-based Li-ion battery based on core–shell MnO@C nanowires and LiMn2 O4 nanoparticles is constructed, and shows high energy density, high-rate capability and ultralong cycle life. Highlights: Core–shell MnO@C nanowires with internal void spaces are fabricated. LiMn2 O4 ∥MnO@C full cell deliver a high energy density of 397 Wh kg −1 . The full cell retains 215 Wh kg −1 even at a high power density of 6.2 kW kg −1 . The full cell sustains a long lifetime with 13% capacity loss over 1000 cycles.